Model-based analysis of multi-UAV path planning for surveying postdisaster building damage - Nagasawa R. (2021)
This study was partly funded by the Japan Society for the Promotion of Science (JSPS) Kakenhi Program (17H06108 and 21H05001); the Core Research Cluster of Disaster Science; the Tough Cyberphysical AI Research Center at Tohoku University, and the National Program for Scientic Research and Advanced Studies (PROCIEN-CIA/CONCYTEC - PERU) [contract number 038-2019 FONDECYT-BM-INC-INV].